New Foods For Thought: Maine Food Producers Add Value through Innovation - Bieman, Betsy (Maine Policy Review, 2011)
This short article discusses how the Maine Technology Institute (MTI) is contributing to the state’s value-added food cluster.
Keywords: Maine; food production